Pengaruh Customer Delight: Justice, Esteem, dan Finishing Touch terhadap Active dan Passive Loyalty (Studi pada Mitra Kerja UPT-PK Singosari-Malang) - Anindita A., Putri (Jurnal Aplikasi Manajemen, 2015)
This research aims to see the impact of variable customer delight that consists ofjustice, esteem, and finishing touch on active and passive loyalty of Co-worker of UPT-PK atSingosari. Based on the organization structure of UPT-PK Singosari, the population of thisresearch is all the third period Students of UPT-PK Singosari in 2013. Based on this population,the sampling technique uses random sampling methods, by involving the students asrespondent. Data analysis uses Structural Equation Modeling (SEM) by using AMOS software.The results show several findings, that justice has positive influence on active andpassive loyalty, esteem has positive influence on active and passive loyalty, finishing touchalso has positive influence on active and passive loyalty to the Co-workers of UPT-PKSingosari.